Leer El Quijote Algunas reflexiones sobre didáctica de la literatura - Estévez Díez, Cristina (Didáctica. Lengua y Literatura, 2006)
In this article it supports the idea of not recommending reading El Quijote to pre-universitary students, because they lack enough knowledge to fully enjoy the book. This would have negative effects on them: keeping students away from developing, deeping and enlarging the joy of reading.
Keywords: Cooperatif reader; Active reading; Joy of reading